If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28k + 36(7 + -1k) = 0 28k + (7 * 36 + -1k * 36) = 0 28k + (252 + -36k) = 0 Reorder the terms: 252 + 28k + -36k = 0 Combine like terms: 28k + -36k = -8k 252 + -8k = 0 Solving 252 + -8k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-252' to each side of the equation. 252 + -252 + -8k = 0 + -252 Combine like terms: 252 + -252 = 0 0 + -8k = 0 + -252 -8k = 0 + -252 Combine like terms: 0 + -252 = -252 -8k = -252 Divide each side by '-8'. k = 31.5 Simplifying k = 31.5
| Graph=2x^2+5 | | Graphy=2x^2+5 | | y^2+6y-23=0 | | x^6y^5= | | 7x^2=56 | | x^6y^3= | | 9x^2+25y^2-50y-56-72x=0 | | (4x+3)(4x+5)=0 | | c=2(pi) | | -3+2=5 | | y=-2x+27 | | b+(-9)=-3 | | X^2+x+42=0 | | 4v^2-15v=4 | | (u+7)(u-6)=0 | | -5m+(-6)=84 | | 6x^4-35x^3+47x^2+15x-9=0 | | x^2+5x+4=100 | | 4v-7+8v+4-5= | | 9+4x=1x+2 | | 5(x-5)(x+5)= | | 6+m/12=18 | | (3z-2)(9+z)=0 | | -6+y=-2-10y | | 36x^2+180x=0 | | -4w(w+1)(w+9)=0 | | b^2-4b-10=0 | | 8b=24+2b | | 999=88+0987 | | 10h=2/3 | | a^4-81b^2= | | 10+9w=-19+19w |